Three-Dimensional Graphene Enhances Neural Stem Cell Proliferation Through Metabolic Regulation - Fang, Qiaojun; Zhang, Yuhua; Chen, Xiangbo; Li, He; Cheng, Liya; Zhu, Wenjuan; Zhang, Zhong; Tang, Mingliang; Liu, Wei; Wang, Hui; Wang, Tian; Shen, Tie; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Graphene consists of two-dimensional sp2-bonded carbon sheets, a single or a few layers thick, which has attracted considerable interest in recent years due to its good conductivity and biocompatibility. Three-dimensional graphene foam (3DG) has been demonstrated to be a robust scaffold for culturing neural stem cells (NSCs) in vitro that not only supports NSCs growth, but also maintains cells in a more active proliferative state than 2D graphene films and ordinary glass. In addition, 3DG can enhance NSCs differentiation into astrocytes and especially neurons. However, the underlying mechanisms behind 3DG’s effects are still poorly understood. Metabolism is the fundamental characteristic of life and provides substances for building and powering the cell, and metabolic activity is tightly regulated during the proliferation, differentiation and self-renewal of stem cells. This study focused on the metabolic reconfiguration of stem cells induced by culturing on 3DG. Metabolomics analysis showed that culturing on 3DG triggered pathways that increased amino acid incorporation and enhanced glucose metabolism, and this suggested some correlation between graphene and pathways involved in Parkinson’s disease. Our work shows that culturing on 3DG induces metabolic reprogramming and contributes to NSCs proliferation and thus provides a very useful starting point for further studies of NSC fate determination on 3DG.